Institusi Pemerintah dan Sistem Pengelolaan Dalam Membangun Good Governance - Ayu, Ayu Restianti; Subaidi, Subaidi (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
This research aims to analyze the condition of public services in Indonesia and describe digital-based pilot public services in Pleret Kapanewon Pleret District, Bantul Regency, Yogyakarta Special Region Province (DIY) in order to create government institutions and management systems in building good governance. This research method uses literature review. Data obtained from the Daily Analysis Opinion column, January 25 2023 Edition published by PT. Media Warta Kencana entitled "Our Public Services Are Still Bad" written by Edward Silaban, an Assistant Ombudsman of the Republic of Indonesia (RI) and Alumni of the Postgraduate History Science University of North Sumatra, and other most accurate online news. The results obtained were that there were 46.42% or 272 agencies classified as green zoned (good), 42.66% or 250 agencies classified as yellow zoned (from bad to good), and 10.92% or 64 agencies classified as red zoned. (bad) (Edward Silaban, 2023). Therefore, in order to improve the quality of public service delivery, it is necessary to carry out reforms in public service systems, processes and procedures so that the people served feel satisfaction with the public services provided by service officers or the government.